Cascading effects from survival to physiological activities, and gene expression of heat shock protein 90 on the abalone Haliotis discus hannai responding to continuous thermal stress. Issue 2 (February 2015) - Park, Kiyun; Lee, Jung Sick; Kang, Ju-Chan; Kim, Jae Won; Kwak, Ihn-Sil
Abstract Increasing temperatures can be a significant stressor for aquatic organisms. Abalones, a type of large marine gastropods, are the most commercially important species in aquaculture for Asia. To evaluate the potential ecological risk posed by temperature stress, we measured biological responses such as survival rate, adhesion ability (falling rate), and foot abnormalities in the abalone Haliotis discus hannai. Additionally, biochemical and molecular responses were evaluated in H. discus hannai exposed to various temperature gradients. The survival rate was reduced in abalones exposed to relative high temperatures (more than 26 °C). Increased temperature stress induced a higher falling rate and abnormal foot structure. Furthermore, increased antioxidant enzyme activities were observed in abalones exposed to relative high temperatures (26 and 28 °C). The activities of superoxide dismutase were induced in a time-dependent manner after high temperature stress. Generally, heat shock protein 90 also increased significantly in H. discus hannai exposed to temperature gradients (more than 24 °C) for 12 h. These results provide valuable information regarding stress responses to increased temperatures, in H. discus hannai: adverse biological and molecular outcomes could be utilized as risk assessments and stress monitoring of marine ecosystems under increased water temperatures.